Szigetköz területfejlesztése a lokális erőforrásokkal - Faragó, Beatrix (Közép-Európai Közlemények, 2024)
The development or underdevelopment of an area partly depends on the utilization of the resources. Neglecting territorial competitiveness can lead to economic and social decline. The study focuses on Szigetköz, where one area development opportunity is the assessment of culture-based innovation capacity and the development of a local strategy. In doing so, they can create a competitive advantage by building on the specific resources of the settlements. The geographical features of Szigetköz are unique, but they have remained unused in terms of development. In addition to strategic analytical methods, the research method includes primary research, using questionnaires and in-depth interviews. The population of Szigetköz and cultural NGOs participated in the survey. The results show the strategic development directions that showed based on the survey deficiencies, but their resources are ready for utilization.